Investigation of liposoluble constituents from the root of Ligularia narynensis (International Journal of Biology and Chemistry, 2018)
In this work, chemical constituents of the liposoluble portion from the root part of medicinal plant Ligularia narynensis have been determined for the first time. The constituents extracted from the root part of L. narynensis by chloroform were analyzed by GC-MS method. Total fifty nine compounds were separated and their relative contents were determined by area normalization in which the major constituents were n-Hexadecanoic acid (13.44%), 9,12-Octadecadienoic acid (Z,Z)- (11.79%), (3aR,4aS,5R,9aS)-5,8-Dimethyl-3-methylene-3a,4,4a,5,6,7,9,9a-octahydroazuleno[6,5-b]furan-2(3H)-one (6.90%), Octadecanoic acid (6.17%), .gamma.-Sitosterol (5.50%), 2(1H)Naphthalenone, 3,5,6,7,8,8a-hexahydro-4,8a-dimethyl-6-(1-methylethenyl)- (4.05%), respectively.